Trade Reforms and Welfare : An Ex-Post Decomposition of Income in Vietnam - Isik-Dikmelik, Aylin (World Bank, Washington, DC, 2012)
This paper analyzes the impact of trade reforms on household welfare. In particular, it studies the importance of each of the links that together constitute the impact using data from the Vietnamese experience in the 1990s. The implementation of trade reforms in the 1990s, most noteworthy of which was the liberalization of rice, resulted in substantial improvement in welfare as evidenced by the drastic decline in poverty. Using analytical and empirical methods, the author examines the role of each channel (direct versus indirect) in this improvement for different groups of households. Results indicate that the growth has been broad based and pro-poor. Poorer households experienced more growth for each and every group analyzed. And contrary to the standard literature, net buyer households had more growth compared with net sellers, emphasizing the importance of indirect links. Decomposition of the growth shows that for rural households, both the direct effect and the multiplier effect drive growth while the multiplier effect was key in urban areas. The importance of the secondary effects underscores the need for a broader model to estimate the impact of trade reforms fully.